Hepatotoxic activity of toluene inhalation and protective role of melatonin - Tas, Ufuk; Ogeturk, Murat; Meydan, Sedat; Kus, Ilter; Kuloglu, Tuncay; Ilhan, Necip; Sarsilmaz, Mustafa (Sage Publications Inc, 2011)
This study was designed to investigate the harmful effects of toluene inhalation in the liver of rats and possible protective effects of melatonin on these detrimental effects. For this purpose, 21 adult male Wistar-albino rats were randomly divided into three equal groups. Animals in group I were used as control. The rats in group II were exposed to toluene (3000 ppm/1 hour/day) for 4 weeks, while the rats in group III were treated with melatonin (10 mg/kg/day, intraperitoneally [ip]) plus toluene inhalation. At the end of the experimental period, liver and blood samples were taken from the decapitated animals. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bilirubin and albumin levels were determined. Liver tissue sections were stained with routine histological methods and examined under the light microscope. In addition, the sections were immunohistochemically stained using avidin-biotin-peroxidase method for determination of apoptosis. The liver tissue activities of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT) and malondialdehyde (MDA) levels were also measured. Toluene inhalation significantly increased serum ALT, AST and tissue MDA, and decreased serum albumin, but did not affect serum ALP, total bilirubin levels and tissue SOD, GSH-Px and CAT activity when compared with controls. The increases in tissue MDA and serum ALT and AST levels induced by toluene inhalation were significantly inhibited by melatonin treatment. In light microscopic observations of tissues from toluene-inhaled rats, massive hepatocyte degeneration, ballooning degeneration and mild pericentral fibrosis were observed. Bax immune reactivity was also increased significantly. Melatonin treatment decreased the balloon degeneration, fibrosis and Bax immune reactivity in the liver of toluene-inhaled rats. In view of the present findings, it is suggested that melatonin has hepatoprotective effects against toluene toxicity via primarily antioxidative properties.
Keywords: Toluene; melatonin; liver; apoptosis; immunohistochemistry